2016
DOI: 10.12659/msm.900257
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Phase Case-Control Study of Autism Risk Among Children Born From the Late 1990s Through the Early 2000s in the United States

Abstract: BackgroundThis study evaluated the hypothesis that the 1999 recommendation by the American Academy of Pediatrics (AAP) and US Public Health Service (PHS) to reduce exposure to mercury (Hg) from Thimerosal in US vaccines would be associated with a reduction in the long-term risk of being diagnosed with autism.Material/MethodsA two-phase assessment utilizing a case (n=73) -control (n=11,783) study in the Vaccine Adverse Event Reporting System (VAERS) database (for hypothesis generating) and a more rigorous, inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A 2014 case-control study of the VAERS revealed that cases diagnosed with the outcomes of autism, speech disorders, or developmental delay were significantly more likely than controls to have received exposure to a Thimerosal-preserved diphtheria-tetanus-acellular-pertussis (DTaP) vaccine (administered from 1997–1999) in comparison to its Thimerosal-reduced formulation (administered from 2004–2006) [ 13 ]. Finally, a 2016 two-phase case-control study revealed a significant reduction in the risk of receiving an autism diagnosis among persons that were born from 1998–2003 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 case-control study of the VAERS revealed that cases diagnosed with the outcomes of autism, speech disorders, or developmental delay were significantly more likely than controls to have received exposure to a Thimerosal-preserved diphtheria-tetanus-acellular-pertussis (DTaP) vaccine (administered from 1997–1999) in comparison to its Thimerosal-reduced formulation (administered from 2004–2006) [ 13 ]. Finally, a 2016 two-phase case-control study revealed a significant reduction in the risk of receiving an autism diagnosis among persons that were born from 1998–2003 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the unanimous, strong, legally-binding and compelling statements by practically all Health Authorities of the entire world declaring that vaccinations are not associated with autism, some recent peer-reviewed papers retrievable in the official scientific database of the US National Library of Medicine of the National Institutes of Health, seem to cast doubts on these certainties. For example, a study published in December 2016 by Authors working in research institutions in Maryland and Texas, uses official data from the Vaccine Adverse Event Reporting System (VAERS) database to conclude that "the risk of autism during from the late1990s to early 2000s in the US significantly decreased with reductions in Hg exposure from Thimerosal-containing childhood vaccines" [5], thus implying that there was an association between Thimerosal-containing vaccines and autism. On the same wavelength is a study published in March 2016 by Authors working at the Center for Biotechnology, the School of Humanities and Social Science and at the Center for Biotechnology of South Carolina who write: "A comprehensive literature search has implicated several environmental factors associated with the development of ASD (Autism Spectrum Disorders).…”
mentioning
confidence: 99%